Antioxidant enzymes expression in lymphocytes of patients undergoing carotid endarterectomy. (January 2020) - Obradovic, Milan; Zafirovic, Sonja; Essack, Magbubah; Dimitrov, Jelena; Zivkovic, Lada; Spremo-Potparevic, Biljana; Radak, Djordje; Bajic, Vladimir B.; Isenovic, Esma R.
Abstract: To remedy carotid artery stenosis and prevent stroke surgical intervention is commonly used, and the gold standard being carotid endarterectomy (CEA). During CEA cerebrovascular hemoglobin oxygen saturation decreases and when this decrease reaches critical levels it leads to cerebral hypoxia that causes neuronal damage. One of the proposed mechanism that affects changes during CEA and contribute to acute brain ischemia (ABI) is oxidative stress. The increased production of reactive oxygen species and reactive nitrogen species during ABI may cause an unregulated inflammatory response and further lead to structural and functional injury of neurons. Antioxidant activity are involved in the protection against neuronal damage after cerebral ischemia. We hypothesized that neuronal injury and poor outcomes in patients undergoing CEA may be results of oxidative stress that disturbed function of antioxidant enzymes and contributed to the DNA damage in lymphocytes.